Biodiversity Science 2000–2026 Mapping International Collaboration and Research Clusters Through Bibliometrics - Judijanto, Loso (West Science Nature and Technology, 2026)
This study aims to examine the evolution of biodiversity science from 2000 to 2026 by mapping global research trends, thematic structures, and international collaboration patterns using a bibliometric approach. Data were collected from the Scopus database based on keywords related to biodiversity, conservation, and ecological sustainability, and analyzed using VOSviewer to generate co-occurrence, overlay, and density visualizations. The results show a significant growth in biodiversity-related publications, reflecting increasing global concern over environmental degradation and climate change. The analysis identifies several major research clusters, including ecological foundations, conservation management, climate change impacts, and emerging interdisciplinary areas such as public health, agriculture, and technological applications. Temporal trends indicate a shift from traditional ecological and taxonomic studies toward integrative and solution-oriented research, particularly involving artificial intelligence and participatory approaches such as citizen science. Furthermore, collaboration networks reveal strong dominance by developed countries, while contributions from developing regions are gradually increasing. This study highlights the transformation of biodiversity science into a multidisciplinary and globally interconnected field and provides insights for future research directions emphasizing inclusivity, innovation, and sustainability.